Check-list of Andalusia (S. Spain) Seaweeds. III. Rhodophyceae - Conde, Francisco; Flores-Moya, Antonio; Soto, Juan; Altamirano, María; Sánchez, Alberto (Acta Botanica Malacitana, 1996)
A check-list of the Rhodophyceae from the Andalusian coast, based on literature records (from 1807 to 1996), is presented. Taxa are listed by provinces. The catalogue contains 348 species and infraspecific taxa under current taxonomy.